PCB153 Disrupts Thyroid Hormone Homeostasis by Affecting its Biosynthesis, Biotransformation, Feedback Regulation, and Metabolism - Liu, C.; Wang, C.; Yan, M.; Quan, C.; Zhou, J.; Yang, K. (Hormone and Metabolic Research, 2012)
PCB153, one of the 3 dominant congeners in the food chain, causes the disruption of the endocrine system in humans and animals. In order to elucidate the effects of PCB153 on the biosynthesis, biotransformation, regulation, metabolism, and transport of thyroid hormones (THs), Sprague-Dawley (SD) rats were dosed with PCB153 intraperitoneally (i.p.) at 0, 4, 16 and 32 mg/kg/day for 5 consecutive days and sacrificed 24 h after the last dose. Results showed that after treatment with PCB153, serum total thyroxine (TT4), total triiodothyronine (TT3), and thyrotropin releasing hormone (TRH) decreased, whereas serum thyroid stimulating hormone (TSH) concentration did not alter. The serum sodium iodide symporter (NIS), thyroid peroxidase (TPO), and thyroglobulin (Tg) levels decreased. The mRNA expressions of type 2 and 3 deiodinases (D2 and D3) reduced, but the type 1 deiodinase (D1) showed no significant change. The TSH receptor (TSHr) and TRH receptor (TRHr) levels declined. PCB153 induced hepatic enzymes, and the UDPGTs, CYP2B1, and CYP3A1 mRNA levels were significantly elevated. Taken together, the observed results from the present study indicated that PCB153 disrupted thyroid hormone homeostasis through influencing synthesis-associated proteins (NIS, TPO and Tg), deiodinases, receptors (TSHr and TRHr), and hepatic enzymes, and the decrease of D3 expression might be the compensatory response of body.
Keywords: PCB153; synthesis-associated proteins; deiodinases; hepatic enzymes